Root system of ‘BRS Platina’ banana under irrigation levels and planting densities - Pereira de Souza, Vitorio Antonio; Santos , Marcelo Rocha dos; Araújo, Agenor Martins de; Costa, Leonardo Teixeira; Donato, Sérgio Luiz Rodrigues (Comunicata Scientiae, 2021)
Banana production stands out in Brazilian semiarid agriculture; however, due to little availability of water resources, associating water-saving technologies with knowledge on parameters involved in the interplay between plants and soil is critical to improving banana production systems. The objectives of this study were to evaluate the effect of planting densities and irrigation levels on root length density of ‘BRS Platina’ banana and to correlate root parameters to crop yield and leaf area. A randomized block design was used, with factors arranged in split plots and treatments replicated three times: four irrigation levels (55%, 70%, 85% and 100% ETc) were assigned to plots and four planting densities (1,600; 2,000; 2,666; and 3,333 plants ha-1) to subplots. Root length density (RLD) was measured at five distances from the pseudostem, longitudinally to a row of plants: 0.10, 0.25, 0.50, 0.75 and 1.10 m; and at three depths for each distance: 0 to 0.20 m, 0.20 to 0.40 m and 0.40 to 0.60 m from surface level. Root length densities were highest at 100% ETc irrigation level and at 2,666 plants ha-1 and 3,333 plants ha-1, within 0.31 m deep and within 0.78 m of the pseudostem. Irrigation interacts with root system, and coupled with higher planting densities, contributes to increasing crop yields of ‘BRS Platina’ banana plants.